Standardization of incidence rates of mesothelioma in the absence of national standards: sensitivity analysis in a cohort formerly exposed to asbestos - Barbiero, Fabiano; Giangreco, Manuela; Pisa, Federica Edith; Negro, Corrado; Bovenzi, Massimo; Rosolen, Valentina; Barbone, Fabio (La Medicina del Lavoro, 2016)
Introduction: The incidence of mesothelioma in Italy shows wide geographical variation, with the highest incidence rates in Genoa and Friuli Venezia Giulia (FVG). For mesothelioma, national standard incidence rates are not available prior to the calendar year 2006. Objectives: To estimate the Standardized Incidence rate Ratio (SIR) of mesothelioma in a cohort of former workers undergoing health surveillance because of previous asbestos exposure, when sex-, age-, and calendar year-specific rates of the national standard are not available and the number of expected cases calculated from the regional rates is biased by the size of the study cohort. Methods: We conducted a sensitivity analysis in a cohort of 2,488 men. We considered every Italian cancer registry available with complete data in the period 1995-2007 (N=14). We calculated, for each year and age group, the corresponding weighted mean rate of 10 registries of North-Italy (Mean W10), the weighted mean rate of all 14 registries available (Mean W14) and considered FVG standard rate. Results: During the period 1995-2007, we observed 25 incident cases of mesothelioma with expected cases that varied between 2.00 (Mean W14) and 2.56 (FVG standard rate), with a SIR of 12.49 (CI95% 8.08-18.48) and 9.76 (CI95% 6.32-14.45) respectively. Conclusions: Our results show that the use of FVG rates as standard does not lead to significant distortions in the calculation of the expected cases. However, distortion is remarkable in the SIRs estimation. Using a weighted mean standard incidence rate may be a valid alternative for SIR estimate when national standard rates are not available.